Considerações acerca do direito de laje: da importância social e das controvérsias quanto ao direito de superfície e ao condomínio Edilício - Gama, Vanessa Dias de Carvalho Quaresma (Universidade Federal Rural do Semi-Árido, 2018)
This study is such an evaluation of the concepts of right of slab and the final proportional means that better represent that institute. The analysis of the right of execution was based on the use of principles of human dignity, the protection of retrogression, the social function of property, the right to housing and the direction of the existing minimum. in which it is inserted. Principle concepts, as well as different legislations of the Brazilian and international legal order were used, besides national judicial decisions for this, several works were used as references of authors like, Rodirgo Mazzei, Ricardo Lira, Cristiano Chaves de Farias, Agnaldo Pereira, Francisco Eduardo Loureiro, Ingo Sarlet, among others. The first chapter aims to present the legislative course undergone by this new law, in addition to its national and international doctrinal origin, allowing to understand the different conceptions of slab. In the second chapter, it was demonstrated that the principles and fundamental rights permeate the land law, such as the right to housing, the principle of human dignity, the social function of property and the prohibition of social retrogression, as well as an analysis of the instrumental character of law of slab to guarantee other fundamental rights for the residents of this urban real estate type. In the third and last chapter of this work, a detailed analysis was carried out on the concepts of slab law, especially with respect to surface law, law conceived as the one that best represented the slab by majority doctrine, and to the condominium building that also has similarities with the institute. Next, it was indicated, from Law 13.465 / 17 and the social demand involved, the concept that would best serve the purpose of the regularization of this institute.
Monografia
Keywords: Direito de laje; Direito de superfície; Condomínio Edilício; Direito sui generis; Dignidade da pessoa humana; CIENCIAS SOCIAIS APLICADAS::DIREITO